Potential value of soluble APPα and APPβ in CSF as biomarkers of dementia disorders: Unresolved issues and perspectives. Issue 4 (21st June 2018) - Araki, Wataru; Araki, Yumiko M; Mizusawa, Hidehiro
Abstract: The significance of fluid biomarkers in the clinical evaluation of dementia disorders has been established. Among such biomarkers, tau (phosphorylated tau and total tau) and amyloid β‐protein 42 (Aβ42) in the cerebrospinal fluid (CSF) stand out as relatively reliable biomarkers of Alzheimer‐type dementia and are now included in recently announced diagnostic guidelines. However, these biomarkers still have some limitations, including variability issues; thus, additional biomarkers would benefit earlier diagnosis of dementia disorders. The CSF soluble amyloid precursor proteins, sAPPα and sAPPβ—direct metabolites of APP produced by α‐secretase– and β‐secretase–mediated cleavage—are potential biomarker candidates. However, there have been conflicting reports on their usefulness as diagnostic biomarkers. In this mini review, we consider recent biomarker studies on sAPPs with a special reference to their relevance to the neuropathology of Alzheimer's disease. We also discuss unresolved issues, such as those relating to methodology, and provide perspectives for future research.